City of gods: the New Jerusalem of John's Revelation in early Christianity - Betz, Nathan (Vigiliae Christianae, 2025)
"This is the story of the great and final city of John's Revelation. Plumbing the first three centuries of Christian literature, this careful narrative highlights the early significance of one of the most influential, evocative, and controversial images in Christian scripture. Chronicling how dozens of early writers, from Justin and Irenaeus to Origen and Methodius, and from the "Montanists" to Tertullian, Victorinus, and Lactantius, imagined and applied the coming New Jerusalem, the study demonstrates how the city, regardless of its myriad and often competing interpretations, always pointed to the highest possible union of God and humanity both here and now and in the age to come"--